Pengaruh Metode Latihan Pliometrik dan Metode Gabungan Latihan Pliometrik dengan Keseimbangan terhadap Performa Lay Up Shoot - Fajri, Ilham Truly; Hidayah, Nida'ul (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2021)
This research discusses the effect of plyometric training method and combined plyometric and balance training method on lay up shoot performance. Lay up shoot is the easiest way to shoot the ball to the ring because this kind of shoot used as close as possible to the ring. The purpose of this research is to determine